Mal de Meleda: A late-diagnosed family with a pathogenic variant not reported from Turkey - Zeynep Karaca; Savaş Yaylı; Sevgi Bahadır (Galenos Publishing House, 2021)
Mal de Meleda (MDM), also called keratoderma palmoplantaris transgrediens, is a rare autosomal recessive palmoplantar keratoderma with an estimated prevalence of 1: 100,000. Genetic mutations affecting SLURP-1 play a role in MDM. It typically starts shortly after birth and is characterized by hyperkeratosis extending from the palmoplantar region to the dorsal surfaces that worsens with age. MDM can lead to severe functional limitations involving the hands and feet and psychosocial problems. The rarity of the condition can lead to misdiagnoses and unsuitable treatments, with MDM commonly mistaken for psoriasis due to the involvement of the elbows and knees. This report presents the case of a family affected by MDM who had a pathogenic variant previously not reported in Turkey, been followed up with the diagnosis of psoriasis for several years, and received a late diagnosis where systemic acitretin achieved satisfactory clinical improvement.